Nobody's hero [large type] - Craven, M. W. (Mike W.), 1968- (Craven, M. W. (Mike W.), 1968- Ben Koenig series, 2025)
"The man who can't feel fear is back. . . When a shocking murder and abduction on the streets of London leads investigators to open a safe in Langley for the first time in ten years, they find a note directing them to four key individuals. Three of the people on the list are dead. The fourth is Ben Koenig. Koenig has no idea why his name is on the list. Then he realizes that he knows the woman who carried out the killing in London. Ten years earlier, without being told why, he was tasked with helping her disappear. Far from being a deranged killer, she is the gatekeeper of a secret that could take down America, and for the safety of the country, she has been in hiding for years until now. And if she has resurfaced, the danger may be closer and more terrifying than anyone can imagine. Ben Koenig has to find her before it's too late. But Ben suffers from a syndrome that means he can't feel fear. He doesn't always know when he should walk away . . . or when he's leading others into danger. [A] story of contract killers, international terrorism, hard choices, and the future of the country and the world as we know it."--